Effect of plant extracts on some quality parameters of canned mixed sweet corn-red bean - Máté, Balázs; Góczán, Bálint; Máté, Mónika (Analecta Technica Szegedinensia, 2023)
The leading export product of Hungary is canned sweetcorn, which is available in single-component or blended varieties with a focus on colour retention, for wich the food industry mainly uses ascorbic acid and EDTA in the brine of canned vegetable. Thoughtful customer behavior is pushing the food industry to switch to natural plant extracts instead of synthetic additives. In order to investigate if acerola plant extract is suitable as a replacement for ascorbic acid, we investigated the potential uses of two varieties of acerola extract in three different concentrations in the case of canned mixed sweet corn and red bean. After production, and after 1 week of thermostating at 55°C and storage at room temperature for 4 and 8 weeks, the changes in pH value, salt concentration, water-soluble dry matter content, colour, total polyphenol content, and antioxidant capacity of the brine were all evaluated in this experiment. The results showed that both acerola extracts were promising in fixing the colour, with the higher application of the first extract and the lowest and highest dosage of the second extract showing the best results. During storage, the polyphenol content and antioxidant capacity of some samples decreased slightly compared to their initial values.